A Review of Flax Fiber Reinforced Thermoset Polymer Composites: Structure and Mechanical Performance - Malik, K. (Taylor and Francis Ltd., 2021)
Flax is a natural fiber that possesses excellent specific properties, low density, safe to handle, eco-friendly, and easily available. These make it exceedingly popular and a potential candidate to replace synthetic reinforcements in polymer composite applications. The thermoset polymer is used for structural application due to its excellent mechanical and interface bonding properties compared to the thermoplastic polymer. Flax-based thermoset polymer composites are becoming popular among researchers for advanced industrial applications. This article is intended to offer a review of the main results presented in the literature on flax fiber-based polymer composites, focusing the attention on the fiber structure, chemical arrangement, physical and mechanical properties. Then, the mechanical performance of pure and hybrid flax fiber reinforced epoxy or polyester composites is comprehensively analyzed. Â© 2021 Taylor & Francis.